Answer:
The expression
is even if both variables (m and n) are even or both are odd
Explanation:
Let's remember the logical operations with even and odd numbers
odd*odd=odd
even*even=even
odd*even=even
odd-odd=even
even-even=even
even-odd=odd
Now, the original expression is:
which can be expressed as:
If m and n are both odd, then:
Then,
If m and n are both even, then:
Then,
Finally if one of them is even, for example m, and the other is odd, for example n, then:
Then,
In conclusion, the expression
is even if both variables (m and n) are even or both are odd. If one of them is even and the other one is odd, then the expression is odd.